Transforming Silica Water Filter Waste into Sustainable Fertiliser - khairul, siti nuratiqah; Ahmad, Sufizar (Research Progress in Mechanical and Manufacturing Engineering, 2025)
This study examines the reuse of silica waste from water filters combined with coffee powder as a sustainable fertilizer. Spinach was selected to evaluate the effects of silica ratios at 0%, 10%, 20%, and 30% on plant growth and soil pH. The combination of 20% silica with 30% coffee powder yielded the tallest plants and the highest number of leaves. Soil pH remained neutral, indicating the stability of the amendment. The findings suggest that this low-cost formulation can improve crop performance. This method also promotes sustainable waste management by repurposing industrial and organic residues.